Marketing And Business Analyst (Studi Kasus: Mr. Klin Laundry Emerald Bintaro) - Sofyan Mufti Prasetiyo; Echa Putra Aditya; Maria Florida Ba Ito; Muhamad Abdul Aziz (CV. Multi Kreasi Media, 2022)
A business analyst is someone whose job is to help analyze a company's processes, systems, products and services, then improve them and make profitable decisions. Marketing analyst is a profession that is responsible for studying market conditions, analyzing competitors, and studying consumer behavior with the aim of selling products. This research contains an explanation of how to analyze SWOT (Strength, Weakness, Opportunity, Treats), trends and factors that can increase consumer buying interest. This study aims to determine the SWOT and trends in Mr Klin Laundry's business. The final results of this study are expected that Mr Klin Laundry's business can find out the SWOT and trends in his business.